Regulation of NK-Cell Function by HLA Class II - Niehrs, Annika; Altfeld, Marcus (Frontiers in Cellular and Infection Microbiology, 2020)
Natural Killer (NK) cells were initially described as part of the innate immune system and characterized by their ability to lyse malignant and virus-infected cells. The cytolytic function of NK cells is tightly controlled by activating and inhibitory receptors expressed on the cell surface. Ligands that interact with a variety of NK-cell receptors include the human leukocyte antigen (HLA) molecules, and the regulation of NK-cell function by HLA class I molecules is well-established. Earlier studies also suggested a role of HLA class II molecules in regulating NK cell activity; yet, interactions between HLA class II molecules and NK cell receptors have not been well-characterized. We recently identified a subset of HLA-DP molecules that can serve as ligands for the natural cytotoxicity receptor NKp44 and activate NK cells. This novel receptor-ligand interaction provides a potential mechanism to explain the strong associations of HLA-DP molecules with HBV infection outcomes, graft-vs.-host disease and inflammatory bowel disease. Furthermore, it adds a new mechanism for NK-cell crosstalk with immune cells expressing HLA class II molecules. In this perspective article, we discuss the potential implications of NK cell receptor interactions with HLA class II molecules for the regulation of immune responses.